2000
DOI: 10.1108/02656710010300144
|View full text |Cite
|
Sign up to set email alerts
|

Quality management implementation in Russia

Abstract: This paper assesses the current knowledge and perceived needs of the key actors in quality management in Russia and examines various strategies for change, in the context of both present Western thinking and the local economic situation and cultural traditions. Three quality management approaches already tested in Russia, namely, third party certification, self-assessment and a Russian/Western hybrid model, all have significant drawbacks. The priority must be for the creation of an educational and institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Most companies in today's global marketplace have realized the importance of raising the quality of goods and services. Quality management is now well established in the USA (Powell, 1995; Rho et al , 2001), Western Europe, and Australia (Mandal et al , 1999), and is increasingly being implemented in developing countries such as China and India (Rao et al ., 1999), and in the emerging markets of Central and Eastern Europe (Dickerson et al , 2000; Krygier, 1993). At the same time, academicians have also been focusing on quality as evidenced by special issues in journals like Decision Sciences , Academy of Management Journal , and California Management Review, and the advent of several new journals such as Quality Management Journal, Journal of Quality Management and Benchmarking for Quality Management and Technology .…”
Section: Introductionmentioning
confidence: 99%
“…Most companies in today's global marketplace have realized the importance of raising the quality of goods and services. Quality management is now well established in the USA (Powell, 1995; Rho et al , 2001), Western Europe, and Australia (Mandal et al , 1999), and is increasingly being implemented in developing countries such as China and India (Rao et al ., 1999), and in the emerging markets of Central and Eastern Europe (Dickerson et al , 2000; Krygier, 1993). At the same time, academicians have also been focusing on quality as evidenced by special issues in journals like Decision Sciences , Academy of Management Journal , and California Management Review, and the advent of several new journals such as Quality Management Journal, Journal of Quality Management and Benchmarking for Quality Management and Technology .…”
Section: Introductionmentioning
confidence: 99%
“…Al Attal (2009), reporting on hospitals in the UAE, stated that the barriers affecting implementation of JCI standards are the relatively high cost of certification arising from training, consultants' fees, registration fees, site visits, etc. Dickenson et al (2000), Al-Haj (2006) and Mostafa (2004) reported the high cost of consultation, implementation and third-party certification fees in Russia. Also, the cost of upgrading the infrastructure to meet international standards and the development costs of certification hindered quality management system (QMS) implementation in Russia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicates that although the RFGQA's design base is that of the EFQM model, it was still adapted to the specific economic situation and needs of Russian organisations as well as their quality maturity. This may provide Russian organisations with a better opportunity to successfully adopt the RFGQA model as Dickenson et al, (2000) comment that the attempted options to implement Western quality management ideas in Russia have shown limited success. In this context, Rocha-Lona et al (2014) suggest that the adoption of quality management models, approaches and tools is in function with different organisation aspects, including how mature a company is in terms of degree of knowledge, use, effective deployment and concrete positive results obtained from a quality management system.…”
Section: Insert Table 2 In Herementioning
confidence: 99%
“…Currently, there is recognition from the Russian government and economic actors of this country that quality management is an important element to effectively compete in the global market and in a relatively open domestic market (Dickenson et al, 2000). Taking into consideration the lack of academic research on the RBEM and the importance placed on quality by the Russian government and organisations, this paper presents a study where the model for business excellence currently employed in Russia is reviewed and its objectives and criteria compared against the three major BEMs (Mavroidis et al, 2007;Miguel, 2001;Sharma and Talwar, 2007), in this case, the MBNQA, EFQM award and Deming Prize.…”
Section: Insert Table 1 In Herementioning
confidence: 99%
See 1 more Smart Citation